2019
DOI: 10.1080/15384101.2019.1618641
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide decrease of DNA replication eye density at the midblastula transition ofXenopus laevis

Abstract: During the first rapid divisions of early development in many species, the DNA:cytoplasm ratio increases until the midblastula transition (MBT) when transcription resumes and cell cycles lengthen. S phase is very rapid in early embryos, about 20-30 times faster than in differentiated cells. Using a combination of DNA fiber studies and a Xenopus laevis embryonic in vitro replication system, we show that S phase slows down shortly after the MBT owing to a genome wide decrease of replication eye density. Increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…We observed that replication origins in post-MBT embryos injected with buffer had an average IOD of 17.6 ± 0.7 Kb and a density of~4-5 origins every 100 Kb ( Supplementary Fig. 8b, c), similar to what previously reported 32 . In embryos injected with SSRP1, instead, we observed a significant stimulation of replication origin assembly with origins placed at an average IOD of 10.1 ± 0.3 Kb and at density of~8-9 origins every 100 Kb (Supplementary Fig.…”
Section: Ssrp1 Accelerates Development By Increasing Cell Cycle Speedsupporting
confidence: 88%
See 2 more Smart Citations
“…We observed that replication origins in post-MBT embryos injected with buffer had an average IOD of 17.6 ± 0.7 Kb and a density of~4-5 origins every 100 Kb ( Supplementary Fig. 8b, c), similar to what previously reported 32 . In embryos injected with SSRP1, instead, we observed a significant stimulation of replication origin assembly with origins placed at an average IOD of 10.1 ± 0.3 Kb and at density of~8-9 origins every 100 Kb (Supplementary Fig.…”
Section: Ssrp1 Accelerates Development By Increasing Cell Cycle Speedsupporting
confidence: 88%
“…Embryonic nucleo-cytoplasmic extracts were prepared as described 32 with some modifications. Briefly, 400 dejellied late blastula (stage 9) embryos were washed in embryo extraction buffer (10 mM Hepes, pH 7.7 KOH, 100 mM KCl, 50 mM Sucrose, 1 mM MgCl 2 , 0.1 mM CaCl 2 and spun at 700 × g for 1 min to pack embryos without crushing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To follow up on this idea, we looked at Plk1 expression during the first embryonic divisions, before midblastula transition (MBT) when the cell cycle is deprived of G1and G2 phases and lasts only 30 min. We found that the level of Plk1 is high during the first rapid cell cycles of development, then suddenly declines at the time when the zygotic transcription resumes and when the cell cycle and the DNA replication program slows down 76 .…”
Section: Discussionmentioning
confidence: 82%
“…A report in Xenopus claimed that injecting dNTPs could increase the number of synchronous embryonic cell cycles [37]. Later studies showed that injecting dNTPs to 2.5-7.5 folds of their endogenous concentration, did neither change the number of synchronous cleavage cycles [20,32], nor the duration of S-phase [38]. Correspondingly, in Drosophila, injection of all four dNTPs did neither affect the number nor the lengths of the embryonic cell cycle.…”
Section: Early Embryonic Cell Cycle and Dynamics Of Dntp Metabolitesmentioning
confidence: 98%